2015
DOI: 10.4103/0019-5413.156202
|View full text |Cite|
|
Sign up to set email alerts
|

Results of reconstruction of massive irreparable rotator cuff tears using a fascia lata allograft

Abstract: Background:Despite the advances in surgical treatment options, massive rotator cuff (r-c) tears still represent a challenge for orthopedic surgeons. This study assesses the effectiveness of fascia lata allograft in reconstruction of massive and irreparable r-c tear and to evaluate the healing and functional outcomes.Materials and Methods:68 patients (38 men, 30 women, mean age 64.9 years) with massive or irreparable r-c tears were treated with placement of fascia lata allograft to fill the defect between Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…50 The remaining 15 GB studies investigated the effect of GB with synthetic grafts, 2,41,49,54 xenograft, 3,24,43 autograft, 40,51,52 and allograft. 6,14,23,29,31 Five SCR studies included observational case series of SCR with autograft 33,34,37 and allograft. 10,33,48 Other study characteristics are summarized in Tables 1 and 2 and Appendix Table A1 (available in the online version of the article).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The remaining 15 GB studies investigated the effect of GB with synthetic grafts, 2,41,49,54 xenograft, 3,24,43 autograft, 40,51,52 and allograft. 6,14,23,29,31 Five SCR studies included observational case series of SCR with autograft 33,34,37 and allograft. 10,33,48 Other study characteristics are summarized in Tables 1 and 2 and Appendix Table A1 (available in the online version of the article).…”
Section: Resultsmentioning
confidence: 99%
“…A specific surgical technique should be performed on appropriately selected cases. Patients with conditions such as preoperative AHI <6 mm, 2,14 high-grade fatty infiltration of the rotator cuff, 40,50 and concomitant reparable subscapularis tear 3,24,43,46 should be carefully considered for GB or SCR.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any osteotomy in this technique allows a reduction of the operative time and a lower risk of complications. The use of banked fascia lata graft has been described for many purposes: reconstruction of osteo-dural defect in neurosurgery, ptosis surgery, urinary incontinence, and rotator cuff tears repair [14][15][16][17][18]. Harvesting of autologous fascia lata can determine postoperative hematoma, wound infection, muscle herniation, weakness of hip flexion, numbness, pain, superficial phlebitis, and cosmetic concern due to the scar [19].…”
Section: Discussionmentioning
confidence: 99%
“…Dimitrios et al in 2015 have shown improvement in pain and CS (from 32.5 to 88.7) in 68 patients treated with interposition of fascia lata allograft for irreparable RCT with a follow-up of 12 months. At the end of 12 months ultrasound examination of 30 patients showed that only three of the patients had retear 61. Pandey et al in 2017 showed in their prospective nonrandomized cohort study of 26 patients having symptomatic irreparable RCT, managed with partial repairs in the first half of patients and with partial repair along with interposition GraftJacket dermal allograft in the second half of patients, that the postoperative scores for the latter group were significantly higher than the former group.…”
Section: Interposition Allograftsmentioning
confidence: 98%